Hospital interior design with healing environment approach - Rangga, Firmansyah; Shaari, Nazlina; Ismail, Sumarni; Yuli, Nensi Golda; Salmarisha, Dinda (AIP Publishing, 2024)
Hospitals are medical facilities that provide comprehensive healing and disease prevention services to communities. Health is a basic human need during life. Health is not only when a person does not have a disease, but a healthy state of body, mental, and social well-being. In recent years, health facilities or hospitals have implemented a healing environment approach that considers the physical, mental, and social aspects of patients and medical staff in hospitals. Five factors must be considered in applying the healing environment: lighting, scenery, social support, privacy, and comfort. The method used in this study was a database search to identify publications related to hospital interior design, health environment, and health care quality. This study was conducted to review the published papers to learn more about the influence caused on patients from aspects in the design of the health environment in hospital buildings. Based on literature search result, creating a health facility with the concept of a healing environment that can help the patient’s healing process and improve staff performance is very important in designing the hospital interior, including natural aspects, sensory aspects, and psychological aspects which are also influenced by considerations of lighting, view, external factors, privacy, and comfort which are divided into six categories including materials, artwork, scenery, visual convenience, acoustic comfort, and orientation.